2014
DOI: 10.1186/1471-2407-14-844
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative anemia on relapse and survival in breast cancer patients

Abstract: BackgroundPrevious studies have shown that preoperative anemia is correlated with the prognoses of various solid tumors. This study was performed to determine the effect of preoperative anemia on relapse and survival in patients with breast cancer.MethodsA total of 2960 patients with breast cancer who underwent surgery between 2002 and 2008 at the Sun Yat-sen University Cancer Center (Guangzhou, PR China) were evaluated in a retrospective analysis. A total of 2123 qualified patients were divided into an anemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 40 publications
3
37
0
2
Order By: Relevance
“…A recent study evaluated the outcome of 367 patients with soft tissue sarcoma and found that low preoperative hemoglobin levels were significantly associated with decreased cancer‐specific survival and OS . Studies from our center have reported that preoperative anemia was an independent predictor of outcome in breast cancer . It should be noted that one similar sized study from Korea showed that preoperative anemia was an independent prognostic factor for TNM stage I‐II GC but not stage III .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent study evaluated the outcome of 367 patients with soft tissue sarcoma and found that low preoperative hemoglobin levels were significantly associated with decreased cancer‐specific survival and OS . Studies from our center have reported that preoperative anemia was an independent predictor of outcome in breast cancer . It should be noted that one similar sized study from Korea showed that preoperative anemia was an independent prognostic factor for TNM stage I‐II GC but not stage III .…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, a study from Zhang et al. also revealed that preoperative anemia was significantly correlated with preoperative nutritional status . In fact, accumulating evidence has indicated that preoperative malnutrition induces poor clinical outcomes .…”
Section: Discussionmentioning
confidence: 97%
“…In this study, low hemoglobin levels at baseline were associated with reduced TTF. Moreover, previous studies associated the low hemoglobin levels including anemia with poor survival prognosis in breast cancer patients [25][26][27][28]. Thus, low hemoglobin levels may be a robust prognostic indicator for reduced TTF for breast cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…The HCT test is often used to check for anemia, usually along with a hemoglobin test or as part of a complete blood count[27]. In previous studies, pretreatment anemia, indicated by low Hb levels, was reported to negatively influence cancer patients’ clinical outcome[28,29], including breast cancer[15]. However, little is known about the prognostic value of HCT in TNBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a research indicates that anemia pretreatment in breast cancer patients might deteriorate the pathological response to neoadjuvant chemotherapy as well as survival status[14]. Moreover, in breast cancer, anemic patients (Hb< 12.0 g/dl) had a worse local relapse-free survival (LRFS), relapse-free survival (RFS), and overall survival (OS) than those without anemia (Hb≥12.0 g/dl), even exclude the influence of clinical stage[15]. …”
Section: Introductionmentioning
confidence: 99%